Modes of Tuberculosis Transmission among New Patients in Blitar District: A Case Study - Mujito Mujito; Suprajitno Suprajitno; Sri Mugianti (Poltekkes Kemenkes Palu, 2025)
Background: Prevention efforts have been carried out massively and early through immunization. However, transmission still occurs, especially to people living in the same house as tuberculosis sufferers. This research aims to describe the mode of transmission and efforts to cure it. Methods: This research design is a case study to uncover the phenomenon of transmission. The participant of this study was 14 new sufferers and 17 old sufferers who were suspected as transmitters selected by purposive sampling. Data collection through in-depth interviews to uncover the phenomenon was carried out from June 2024 to April 2025. Data analysis used the Miles and Huberman model was continued with triangulation validation to program holders at the Puskesmas. Results: Old and new sufferers were found in childhood. New sufferers were found in 8 people including infant, when diagnosed was 18 days old. New sufferers were infected during activities in the school environment transmitted by school friends and also infected from adults in the household. The transmission that occurred was not realized by new sufferers because it could be caused by unexpected people, even those closest to them. Transmission easily occurs if individuals live in the same house as an infected person and have a weak immune system. The danger of transmission to children can lead to stigma from peers and the community. Preventive measures that everyone should maintain include healthy behaviors such as consuming nutritious food, wearing a mask, covering when coughing, and avoiding spitting carelessly. Conclusion: Children are highly vulnerable, and prevention efforts need to be enhanced through healthy behaviors.